The Impact of Internal Control System on the Accountability Practices in Waqf Institutions: Evidence from Al Rahma International Waqf - Mohammed M. Ahmed Ayedh; Nurul Nazlia Binti Jamil; Mohammad Tahir Bin Zainuddin (IISE International Knowledge Sharing Platform, 2024)
Non-Indexed Publication